Sierpenski gasket monopole antenna design - A. Rahim, Mohamad Kamal (2005)
The use of fractal geometry in designing antenna has been a recent topic of interest. It have already proved that fractal shaped have their own unique characteristics that improved antenna achievement. This paper presents about one of familiar geometry in fractal antenna, Sierpenski gasket monopole antenna is proposed for a multiband application. Two different dimension of the antenna has been designed and investigated. The design achieves a good multiband throughout the frequency range from 1 to 10 GHz for both designed.